Review on In Silico Methods, High-throughput Screening Techniques, and Cell Culture Based In Vitro Assays for SARS-CoV-2 - Cetin, Yuksel; Aydinlik, Seyma; Gungor, Aysen; Kan, Tugce; Avsar, Timucin; Durdagi, Serdar (Current Medicinal Chemistry, 2022)
The COVID-19 outbreak caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) continues to have high incidence and mortality rate globally. To meet the increasingly growing demand for new therapeutic drugs and vaccines, researchers are developing different diagnostic techniques focused on screening new drugs in clinical use, developing an antibody targeting a SARS-CoV-2 receptor, or interrupting infection/replication mechanisms of SARS-CoV-2. Although many prestigious research publications are addressing this subject, there is no open access platform where all experimental techniques for COVID-19 research can be seen as a whole. Many researchers have accelerated the development of in silico methods, high-throughput screening techniques, and in vitro assays. This development has played an important role in the emergence of improved, innovative strategies, including different antiviral drug development, new drug discovery protocols, combinations of approved drugs, and setting up new drug classes during the COVID-19 outbreak. Hence, the present review discusses the current literature on these modalities, including virtual in silico methods for instant ligand- and target-driven based techniques, nucleic acid amplification tests, and in vitro models based on sensitive cell cultures, tissue equivalents, organoids, and SARS-CoV-2 neutralization systems (lentiviral pseudotype, viral isolates, etc.). This pack of complementary tests informs researchers about the accurate, most relevant emerging techniques available and in vitro assays allow them to understand their strengths and limitations. This review could be a pioneer reference guide for the development of logical algorithmic approaches for new drugs and vaccine strategies against COVID-19.
Keywords: COVID-19